A biopsychosocial perspective on parenting and developmental psychopathology. (17th December 2013) - Calkins, Susan D.; Propper, Cathi; Mills-Koonce, W. Roger
Abstract: Although considerable research has examined the relations between parental behavior and a range of child developmental outcomes, much of this work has been conducted at a very broad level of behavioral analysis. A developmental psychopathology framework and recent research conducted within this framework point to the need for models of parenting and child psychopathology that offer greater specificity regarding processes that may be implicated in the effects of these relationships. In addition, recent animal work and some human work has focused more on the proximal biological and social mechanisms through which parenting affects child outcomes. Our conceptualization of parenting effects acknowledges that family and child factors are embedded in a dynamic biological and social context that is key to understanding developmental trajectories of child adjustment. In this paper, we review two areas of research that are illuminating the biological processes underlying links between parenting and child psychopathology: molecular genetics and psychophysiology. We adopt a biopsychosocial perspective on developmental psychopathology that implies that a set of hierarchically organized, but reciprocally interacting, processes, from the genetic to the environmental, provide the essential elements of both normative and nonnormative development (Gottlieb, 2007). New directions stimulated by this general approach are discussed, with an emphasis on the contextual and developmental issues and applications implied by such a perspective.